Posted by Anonymous on Thursday, August 9, 2012 at 9:16am.
Given the following system is consistent
Find the exact value of t.
- Math - Reiny, Thursday, August 9, 2012 at 10:31am
subtract the first from the second
xt - x = t-1
x(t-1) = t-1
x = 1, if tą1
1+y = 1
y = 0
in the last:
(1+t)(1) + 0 = 3
1+t = 3
t = 2
- Math - drwls, Thursday, August 9, 2012 at 10:35am
Subtracting the first equation from the second gives you:
t-1 = (t-1)x
Therefore x = 1.
The first equation tells you that y = 0.
The third equation requires that
1 + t = 3
t = 2
Answer This Question
More Related Questions
- Maths - Solve the following system of linear equations by addition. Indicate ...
- Math (College Pre-Cal) - The exact conversion between the English measurement ...
- Pre-calculus - Find the value for c for which the system is consistent and ...
- Algebra-Multiple choice - Hello, I have some practice math I'm working through ...
- Math - Describe the system 6x-2y=10 and 9x-3y=8 as consistent and independent, ...
- math - An initial-value problem is given by the differential equation, f(x,y) = ...
- biology - I need a general principle found to be consistent through the ...
- Algebra - Describe the system 6x-2y=10 and 9x-3y=8 as consistent and independent...
- Math - Arithmetic & Geometric - 1) Given the terms a35 = 1238 and a70 = 1483 of ...
- Math - 1. Find the exact value of 2tan pi/12 / 1-tan^2 pi/12 root 3/3? 2. Given ...